Pengembangan Media ProFiZ (Profesional Fiqih Zakat) Berbasis Website pada Kelas X di MA Unggulan KH. Abd. Wahab Hasbullah Tambakberas Jombang - Firda Zajilah Rohmah; Hidayatur Rohmah (Lembaga Yasin AlSys, 2025)
This study focuses on the development of the ProFiZ (Profesional Fiqih Zakat) web-based learning media for Grade X students at MA Unggulan KH. Abd. Wahab Hasbullah Tambakberas Jombang, and evaluates students’ responses to its use. The research is driven by the need for interactive, valid, and practical media to support fiqih learning, particularly in the subject of zakat. The method used is Research and Development (RnD) following the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The media product was validated by media and content experts, then tested with students as end users to assess its feasibility. Validation results showed scores of 89% from the media expert and 94% from the content expert, both classified as “highly valid.” Field testing through questionnaires yielded a student response score of 91%, categorized as “highly practical.” Therefore, the ProFiZ media is considered highly valid and highly practical for use in fiqih zakat instruction and effectively increases student engagement with the subject matter.